A monomeric, heterobimetallic complex with an unsupported Mg−Fe bond - Birchall, Christopher; Moxey, Graeme J.; McMaster, Jonathan; Blake, Alexander J.; Lewis, William; Kays, Deborah L. (Elsevier, 2017)
The phosphinimine, trimethylsilyl-substituted BIPM ligand [BIPM = bis(iminophosphorano)methanide] has been used to stabilise CH(Ph2PNSiMe3)2MgFe(η5-C5H5)(CO)2 (1), which is a structurally authenticated complex exhibiting a direct, unsupported bond between an alkaline earth metal and a transition metal. The FTIR-measured carbonyl stretching frequencies for this complex suggest that there is a polarisation of charge from the transition metal fragment to the magnesium centre. The presence of a polar metal-metal bond in 1 is confirmed by DFT calculations, which suggest that the Mg−Fe bond is predominantly ionic in nature.